Encouraging Pro-Feminist Public Policy through Gender Watch Movement: Studies in Gresik Regency - Iva Hasanah (Jurnal Perempuan, 2017)
Gender Watch is a strategy to advocate policy that is based on pro-women data. Gender Watch is developed to improve access and participation of poor and marginalized women to government social protection. The improvement of access started with the development of poor women capacity and organizing in grass root level with the establishment of Women School in Gresik Regency. In this school, women collect data, work with many stakeholders, submit the obtained data to the policy maker, and oversee the Regional Development Planning Forum (Musrenbang) in the village up to the regency. The work and the contribution of Women School in development force the Gresik Regional Government to be committed to allocate the budget for Women School and to replicate Women School in several villages. The commitment of the regional government is included in Mid-Term Regional Development Plan (RPJMD), City Work Plan (RKPD), and Regent’s regulation. The paper outlines the process and the experience of organizing in the grass root level and the data-based advocacy effort, so the policy advocacy strategy that stresses on the organizing of the grass root women through women schools, attracts the attention of the regional government to allocate the budget in the village level up to the regency level.